In vivo conversion of astrocytes to myelinating cells by miR‐302/367 and valproate to enhance myelin repair. (27th January 2017) - Ghasemi‐Kasman, Maryam; Zare, Leila; Baharvand, Hossein; Javan, Mohammad
Abstract: Enhancement of repair potential for degenerative brain diseases has been a research priority during recent years. Considering recent advancements in the field of direct transdifferentiation, conversion of astrocytes as a prominent component of glial scars to the progenitor cells that contribute to the repair mechanisms seems interesting. Recently, we have reported miR‐302/367‐mediated in vivo conversion of astrocytes into neuroblasts and neurons. In the current study, we used miR‐302/367 and valproate (VPA) to show the possibility of conversion of astrocytes to oligodendrocyte progenitor cells and myelinating cells in a cuprizone (CPZ)‐induced model of demyelination. Evaluation of behavioural impairment following CPZ and consequent to the treatments showed functional recovery from impairments. Enhanced remyelination was detected by luxol fast blue staining and immunostaining against two mature myelin markers, myelin basic protein and proteolipid protein. Tracing of transduced cells with green fluorescent protein showed their contribution toward generation of new myelinating cells. These findings have suggested that in vivo specific targeting of astrocytes for forced expression of the miR‐302/367 cluster and VPA administration may increase the brain's potential for repairing myelin insults by the generation of oligodendroglia from astrocytes. This finding may open a new avenue for enhancement of brain repair in neurodegenerative diseases such as multiple sclerosis. Copyright © 2017 John Wiley & Sons, Ltd.